2023
DOI: 10.3389/fenvs.2022.1060277
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biochar and vermicompost on microorganisms and enzymatic activities in greenhouse soil

Abstract: The effects of different contents of biochar and vermicompost on the microbial and enzymatic activities of greenhouse soil were determined to provide a theoretical basis for improving the quality of greenhouse soil. The experiment was conducted in a greenhouse using potted tomatoes. Five treatments consisted of different amount ratios of organic amendments: 1% biochar (BC1), 3% biochar (BC3), 5% biochar (BC5), 3% vermicompost (VC3), and 5% vermicompost (VC5), with no addition of organic amendments as the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 65 publications
2
17
0
1
Order By: Relevance
“…Most studies have focused on the positive effect of biochar on enzyme activity. The explanation for this is that biochar contains a large amount of nutrients, which can improve the physical and chemical properties of the soil, thereby stimulating enzyme activity (Sopena & Bending, 2013; Wu et al, 2023). Of course, it is also necessary to consider that different types and properties of biochar have different effects on enzyme activity (Futa et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have focused on the positive effect of biochar on enzyme activity. The explanation for this is that biochar contains a large amount of nutrients, which can improve the physical and chemical properties of the soil, thereby stimulating enzyme activity (Sopena & Bending, 2013; Wu et al, 2023). Of course, it is also necessary to consider that different types and properties of biochar have different effects on enzyme activity (Futa et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…(2017) , where it was reported that phosphatase activities significantly peaked under BC applied at the rate of 20 t/hm 2 . This phenomenon is associated with the crucial role BC utilization plays in decomposing organic matter, which eventually releases organic phosphorus compounds ( Wu et al., 2023 ). However, BC-supplemented soil has also been observed to lower the enzymatic activities tied to ecological processes such as soil C mineralization ( Lehmann et al., 2011 ), primarily due to the high C content in BC ( Panwar et al., 2019 ) or the sorption of enzymes by BC ( Czimczik and Masiello, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…These views can also be confirmed by the soil fertility enhancement after pepper harvest in this study ( Table 5 ). Notably, the addition of vermicompost may further enhance the soil amendment effect of biochar because of the richness of vermicompost in beneficial microorganisms, which can further activate and colonize the pore structure of biochar ( Zhao et al., 2020 ; Wu et al., 2022 ). Furthermore, vermicompost contains beneficial microorganisms that can inhibit the growth of pathogenic fungi by inducing the secretion of antibacterial substances, including antibiotics and cell wall-degrading enzymes, particularly in soils with continuous cropping barriers ( Szczech et al., 1993 ; Xiao et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%